The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7869/djo.60
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Pseudo Foster Kennedy Syndrome In a HIV Positive Patient

Abstract: A 39 year old male patient presented with complaints of sudden onset diminished vision in the right eye since two weeks and in the left eye since four days associated with painful ocular movements. On examination patient had optic disc edema in the right eye and the left eye showed optic disc pallor. Patient was also suffering from human immunodeficiency virus (HIV) infection. In this case study we report that the patient had pseudo Foster Kennedy syndrome directly attributed to HIV. Patient was started on int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…(Figure 4) with findings in other reported cases of pseudo-Foster Kennedy syndrome PFKS which were secondary to other causes, such as NAION and vitamin B12 deficiency. 6,7 However, Trikey et al reported an enlarged blind spot with peripheral field constriction over the eye with optic disc swelling and generalized depression in the eye with optic atrophy. 8 OCT RNFL of our patient showed generalized thinning in the eye with optic atrophy and normal thickness in the eye with swollen optic disc.…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 4) with findings in other reported cases of pseudo-Foster Kennedy syndrome PFKS which were secondary to other causes, such as NAION and vitamin B12 deficiency. 6,7 However, Trikey et al reported an enlarged blind spot with peripheral field constriction over the eye with optic disc swelling and generalized depression in the eye with optic atrophy. 8 OCT RNFL of our patient showed generalized thinning in the eye with optic atrophy and normal thickness in the eye with swollen optic disc.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudo Foster Kennedy syndrome[9] - one-sided optic atrophy with papilledema in the other eye but without any space occupying lesion. HIV infection rarely could be a predisposing factor for this syndrome.…”
Section: Pseudo Conditions In Clinical Groupmentioning
confidence: 99%